The impacts of intellectual capital on competitive advantage mediated by organizational performance in selected Malaysia research universities - Alkhateeb, Abdullah Nihad (2019)
Nowadays, the traditional tangible capitals like cash, buildings, and inventories are the effective weapons for organizational survival can not longer be counted in alone. Since knowledge becomes vital in leading economy currently, the importance of the intangible assets or the so-called intellectual capital has emerged. One of such importance identified in intellectual capital literature is gained competitive advantage. However, researches testing the effects of intellectual capital on competitive advantage in universities is limited. Therefore, this study sought to address this research gap. Underpinned by resource-based view theory and knowledge-based view theory, this study examined the relationships between intellectual capital components and competitive advantage of Malaysia research universities with organizational performance as a mediating variable embedded in the framework. The quantitative methods were adopted and the survy data collection method was used. Further, the study sample comprised 473 management employees of public research universities in Malaysia were taken by sample random technique. The formulated hypotheses were tested using Partial Least Squares - structural equation modelling. The results showed that human capital, relational capital, social capital, renewal capital, trust capital, and entrepreneurial capital had a significant prediction as the components of intellectual capital on the competitive advantage in Malaysia research universities, while the structural capital and technological capital showed insignificant prediction. Secondly, the intellectual capital components had a significant prediction on organizational performance, except structural capital, relational capital, technological capital, trust capital, and entrepreneurial capital. Thirdly, the organizational performance significantly predicted on competitive advantage. Lastly, in this study, the organizational performance mediated the relationship between human capital, social capital, spiritual capital, renewal capital and competitive advantage. Thus, this study contributes to the literature on intellectual capital in Malaysian research universities. Specifically, this study believed that the conceptual relationship proposed provided a useful and robust framework that can offer universities management valuable information on the factors that influence the competitive advantage of the university. Thus, the ministry of higher education has to be reviewed education, training, and employment policies, particularly to recruit staffs that have the skills necessary for the development of research activities, and develop effective strategies that will achieve the universities goals, to be on par with the other world-class universities, as well as to achieve significant for Malaysia in higher education in the process of discovery and creation of new knowledge.